2019
DOI: 10.1121/1.5123176
|View full text |Cite
|
Sign up to set email alerts
|

Hemisphere-specific properties of the ventriloquism aftereffect

Abstract: Visual calibration of auditory space requires re-alignment of representations differing in (1) format (auditory hemispheric channels vs visual maps) and (2) reference frames (head-centered vs eye-centered). Here, a ventriloquism paradigm from Kopčo, Lin, Shinn-Cunningham, and Groh [J. Neurosci. 29, 13809–13814 (2009)] was used to examine these processes in humans for ventriloquism induced within one spatial hemifield. Results show that (1) the auditory representation can be adapted even by aligned audio-visual… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(36 citation statements)
references
References 15 publications
1
34
1
Order By: Relevance
“…A possible explanation of this difference is that the current experiment was performed in a real reverberant room and the subjects were provided with a level-independent auditory distance cue, the direct-to-reverberant energy ratio, whereas in the Gardner study no such cue was available and the subjects likely relied on guessing. The observed constant 72% weight given to the V-component in the current study is much smaller than the weight typically observed in horizontal studies, in which this weight is commonly around 90% (e.g., Kopčo et al 2019).…”
Section: Discussioncontrasting
confidence: 72%
“…A possible explanation of this difference is that the current experiment was performed in a real reverberant room and the subjects were provided with a level-independent auditory distance cue, the direct-to-reverberant energy ratio, whereas in the Gardner study no such cue was available and the subjects likely relied on guessing. The observed constant 72% weight given to the V-component in the current study is much smaller than the weight typically observed in horizontal studies, in which this weight is commonly around 90% (e.g., Kopčo et al 2019).…”
Section: Discussioncontrasting
confidence: 72%
“…A means of aligning these RFs is necessary by the stage at which the visual signals guide auditory spatial adaptation. Our previous studies suggest that a mixture of eye-centered and head-centered RFs is associated with recalibration in the central region of the audiovisual field [12] while the head-centered RF dominates for VAE locally induced in a single hemifield in the visual periphery [13].…”
Section: Introductionmentioning
confidence: 96%
“…Finally, Kopco et al [13] observed a new adaptive phenomenon induced by aligned audiovisual stimuli presented in the periphery, exhibited as a shift in responses to sounds Loksa presented alone in the central region. The shift magnitude depended on the gaze direction and, thus, was at least partly in the eye-centered RF.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations